Tren E-Commerce Mempengaruhi Keputusan Pembelian: Studi Kasus Pengguna Shopee Pada Mahasiswa Tata Boga Unimed - Giatman; Ganefri; Yuzia Eka Putri; Asmar Yulastri; Hansi Effendi; Mukhlidi Muskhir; Refdinal; Syah, Nurhasan (The Indonesian Journal of Computer Science, 2023)
The online shopping trend on Shopee and other e-commerce platforms continues to develop and has controversy and occurs from time to time. Some sellers on Shopee have been involved in fraud, such as sending fake products or not sending products at all. This can harm buyers and damage Shopee's reputation. This research aims to analyze the influence of trends in the use of e-commerce (Shopee) on the purchasing decisions of culinary students at Unimed. This research uses a quantitative approach. The sample in this study was 93 culinary students from the class of 2023. The data analysis techniques used are the t test, f test and coefficient of determination. The results of the test analysis show a sig value of 0.000, which means that there is an influence from the e-commerce usage variable (X) on the purchasing decision variable (Y). The strength of influence of the e-commerce usage variable influences the purchasing decision variable by 46%. Meanwhile, the remaining 0.540 or 54% is influenced by other variables studied.